Analyzing Methotrexate’s Impact on Oxidative Stress Indicators in Breast Cancer Cells - Durmuş, Sinem; Düzgün Ergün, Dilek; Gelişgen, Remise; Bakır, Nihal; Uzun, Hafize (Cerrahpaşa Medical Journal, 2025)
Objective: Methotrexate (MTX) is one of the most commonly used antiproliferative chemotherapeutic agents. In addition to its antiproliferative effect, MTX may also play a role in the induction of oxidative stress. This study investigates the effects of MTX on cell cytotoxicity and oxidative stress markers (superoxide dismutase [SOD] activity, malondialdehyde [MDA] levels), and total thiol content) in both human healthy breast cells (hTERT-HME1) and human breast cancer cells (MCF-7). Methods: The hTERT-HME1 and MCF-7 cell lines were divided into untreated control and MTX groups. The cell viability assay was carried out using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Superoxide dismutase, MDA, and total thiol levels were measured spectrophotometrically. Results: The effects of MTX on cell viability were observed after treatment of hTERT-HME1 and MCF-7 for 24, 48, and 72 hours. In comparison to MCF-7 cells, hTERT-HME1 cells exhibited increased cell survival and half-maximum inhibitory concentration 50 values after MTX treatment. Methotrexate administration also significantly decreased SOD and total thiol levels and increased MDA levels in both cell types. Conclusion: This study suggests that MTX has high anticancer activity through its effects on cell viability and oxidative stress. However, observation of similar effects in healthy cells requires the development of various combination therapies or targeted drug delivery systems to reduce the side effects of MTX. Cite this article as: Durmuş S, Ergün DD, Gelişgen R, Bakır N, Uzun H. Analyzing methotrexate’s impact on oxidative stress indicators in breast cancer cells. Cerrahpaşa Med J 2025, 49, 0007, doi: 10.5152/cjm.2025.25007.